Actualising (Overlooked) Material Capacities. (September 2015) - Kolarevic, Branko; Menges, Achim
<x xml:space="preserve">Abstract</x> An emphasis on material synthesis is not without its pitfalls and challenges. Here Branko Kolarevic, Professor and Chair in Integrated Design at the University of Calgary Faculty of Environmental Design, alerts us to the dangers of overlooking materials' shifting capacities, which are so often scale dependent, while also disregarding existing materials in favour of the new or novel. As the potential grows for material systems in buildings to become more adaptive and to harness automation, Kolarevic describes some exciting developments that are taking place in dynamic facade design, providing the much‐heralded promise of an efficient use of ambient energy.